The epileptology of GNB5 encephalopathy. (20th October 2019) - Poke, Gemma; King, Chontelle; Muir, Alison; de Valles‐Ibáñez, Guillem; Germano, Michele; Moura de Souza, Carolina F.; Fung, Jasmine; Chung, Brian; Fung, Cheuk Wing; Mignot, Cyril; Ilea, Adina; Keren, Boris; et al.
Abstract: Pathogenic variants in GNB5 cause an autosomal recessive neurodevelopmental disorder with neonatal sinus bradycardia. Seizures or epilepsy occurred in 10 of 22 previously reported cases, including 6 children from one family. We delineate the epileptology of GNB5 encephalopathy. Our nine patients, including five new patients, were from seven families. Epileptic spasms were the most frequent seizure type, occurring in eight of nine patients, and began at a median age of 3 months (2 months to 3 years). Focal seizures preceded spasms in three children, with onset at 7 days, 11 days, and 4 months. One child presented with convulsive status epilepticus at 6 months. Three children had burst suppression on electroencephalography (EEG), three had hypsarrhythmia, and one evolved from burst suppression to hypsarrhythmia. Background slowing was present in all after age 3 years. Magnetic resonance imaging (MRI) showed cerebral atrophy in one child and cerebellar atrophy in another. All nine had abnormal development prior to seizure onset and ultimately had profound impairment without regression. Hypotonia was present in all, with contractures developing in two older patients. All individuals had biallelic pathogenic variants in GNB5, predicted by in silico tools to result in protein truncation and loss‐of‐function. GNB5 developmental and epileptic encephalopathy is characterized by epileptic spasms, focal seizures, and profound impairment.